PROBLEMS OF NURSE TRAINING IN MEDICAL COLLEGES AND ACADEMY AT THE CURRENT STAGE OF MEDICAL EDUCATION DEVELOPMENT (Physical Culture and Sport: Scientific Perspective, 2022)
The article examines the problem of training nurses in colleges and academies. The state of readiness of mid-level medical workers to work in extreme conditions has been determined. For this purpose, medical colleges are developing a system of career guidance work with students at various stages of professional formation. Multilevel education and various factors (psychodynamic, intellectual, personal and socio-psychological properties) affecting the effectiveness of the professional growth of specialists are taken into account. The model and individual elements of the psychological support program that can be used in the process of forming the readiness of future nurses for professional activity are proposed. The training of future nurses is consistent with world standards, which is especially important in the conditions of hostilities. Among the urgent tasks of training bachelors in medical affairs, the problem of professionally competent workers is being considered, ways of training professionally competent medical specialists are being worked out. The essence of the terms "training", "professional training of nurses", "career orientation", "professional competence" is analyzed. The role of competence and system approaches in the training of nurses in Ukraine and abroad is shown. Ways to improve the training of nurses in the conditions of martial law have been identified, among which the main attention is paid to modern pedagogical technologies, interactive teaching methods, mixed learning, and practical training. Distance education and training programs for nurses in military conditions are being developed.
Keywords: middle-level medical worker; medical college; training; professional competence; ways of improvement; peculiarities of training in wartime